KONSELING KELOMPOK COGNITIVE BEHAVIORAL TERAPHY UNTUK REMAJA KECANDUAN K-POP - Zulfikar Fadhlullah; Netrawati; Yeni Karneli (CV Putra Publisher, 2023)
This paper aims to explain counseling adolescents who are addicted to k-pop through cognitive behavioral therapy. Teenagers who use gadgets are increasing. The impact of its use can be positive and negative. However, k-pop addiction among teenagers has a negative impact so they tend to forget their study assignments, forgetting to fulfill basic needs such as eating, drinking, bathing, and having problems sleeping. Of course, teenagers who experience the negative effects of k-pop need cognitive behavioral therapy by a counselor. The method used in this paper is library research (Library Research). The approach used is a group counseling approach with the theory of cognitive behavioral therapy. This paper concludes that adolescents who are addicted to k-pop can be treated through cognitive behavioral counseling which refers to cognitive correction that is distorted due to events that harm them both physically and psychologically. Through this therapy, adolescents who are experiencing biological, cognitive, and emotional changes can recover to control themselves.